2012
DOI: 10.1158/1078-0432.ccr-11-2181
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II Trial of Carboplatin and Paclitaxel Chemotherapy in Combination with Intravenous Oncolytic Reovirus in Patients with Advanced Malignancies

Abstract: Purpose Reovirus type 3 Dearing (RT3D) replicates preferentially in Ras-activated cancers. RT3D shows synergistic in vitro cytotoxicity in combination with platins and taxanes. The purpose of this phase I/II study was to assess RT3D combined with carboplatin/paclitaxel in patients with advanced cancers. Experimental Design Patients were initially treated in a dose-escalating, phase I trial with intravenous RT3D days 1 to 5, carboplatin [area under curve (AUC) 5, day 1] and paclitaxel (175 mg/m2, day 1) 3-wee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
118
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(125 citation statements)
references
References 22 publications
1
118
1
Order By: Relevance
“…This study concluded that reovirus antitumor activity is unaffected by high doses of radiation, and that the combination of the two is safe for further investigations. Following the initial study, a subsequent Phase II trial 69 was performed using low-dose radiation, and demonstrated a 93% total disease-control rate (combined CR, PR, and SD) in treated lesions, thereby confirming the safety and positive clinical outcomes of the combination regimen. As opposed to palliative radiotherapy, it is expected that reovirus will be used in future trials in combination with radical radiotherapy for a curative intent.…”
Section: Combination Therapy With Reovirus In Clinical Studiesmentioning
confidence: 86%
See 2 more Smart Citations
“…This study concluded that reovirus antitumor activity is unaffected by high doses of radiation, and that the combination of the two is safe for further investigations. Following the initial study, a subsequent Phase II trial 69 was performed using low-dose radiation, and demonstrated a 93% total disease-control rate (combined CR, PR, and SD) in treated lesions, thereby confirming the safety and positive clinical outcomes of the combination regimen. As opposed to palliative radiotherapy, it is expected that reovirus will be used in future trials in combination with radical radiotherapy for a curative intent.…”
Section: Combination Therapy With Reovirus In Clinical Studiesmentioning
confidence: 86%
“…[69] All aforementioned combinations have gone on to further Phase II or Phase III clinical trials. In either monotherapy or combination therapy studies, the recommended dose of reovirus is 3×10 10 TCID 50 once over 60 minutes on days 1-5 every 3 or 4 weeks.…”
Section: Combination Therapy With Reovirus In Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a phase I/II trial of REOLYSIN and carboplatin and paclitaxel chemotherapy, of the 31 patients who were evaluable, 1 patient had a complete response, 6 patients had partial response, and 9 patients had stable disease (52). The success of this study led to the launch of a phase III, randomized, double-blind study in patients with platinum-refractory head and neck cancers (NCT01166542).…”
Section: Combination Chemotherapymentioning
confidence: 99%
“…nAbs bind virus and subsequently block viral attachment to cellular surface receptors, inhibiting viral infection and replication. Immunologic analysis of patients enrolled in reovirus clinical trials has consistently detected circulating nAbs (47,52,70). This humoral immune response presents a significant barrier to intravenously administered reovirus reaching, colonizing, and eliminating disseminated tumor beds.…”
Section: Combination Immunotherapymentioning
confidence: 99%